The effect of vortex structures in the river bed on the concentration and size differentiation of the fish population - A. A. Chemagin (Biosystems Diversity, 2018)
On the basis of recent hydroacoustic method with using “PanCor” computerized program-technological complex, research was conducted on the distribution of fish of different taxonomic groups in the water area of Irtysh, a large trans-border river on the bend (meander) with a vortex zone. A hydroacoustic complex allows one to conduct remote size-taxonomic identification of fish. It is demonstrated that on the examined area of the river, fish of different taxonomic groups and sizes concentrate in the zones of increased turbidity and intense whirlpools (vortices) which form as a result of opposite currents at the river meander. The largest concentrations of fish form in the deepest zone of the examined water area and in front of it – vortex zone. It was determined that in the zone of recorded vortices, the number of fish of different taxonomic groups (Cyprinidae, Percidae, Coregonus, Esocidae, Sturgeon, burbot) is on average 2.14–2.61 times reliably higher compared to the observations at the studied part of the river with no vortices at comparable parameters of depth. The size structure of the fish was dominated by small individuals (<10 cm) in the vortices, and large fish out of these zones, which can be an additional element of the survival strategy. The peculiarities of the studied area of the river with vortices, on one hand, are the factors of formation of fish concentrations, and on the other hand – factors of differentiation by taxonomical and size parameter, related to inability of certain groups of organisms to resist the hydrodynamic force of the vortex structure.